Síntese de redes de trocadores de calor usando conceitos de flexibilidade e controlabilidade - Miranda, Camila de Brito (2016)
Synthesis of heat exchanger network (HEN) is a subject of great industrial interest. In an industrial process it is possible to take advantage of the existing energy in its own process streams and consequently to reduce spending on utilities. Operability considerations are important for the HEN design due to the uncertainties in streams temperature and flow rates, which are very common in real operations. Thus, studies were performed in this work to meet, in addition to economic interests, flexibility, controllability and resiliency aspects of the HEN. It was proposed an optimization model formulated as a mixed integer nonlinear programming problem (MINLP) in order to minimize the total annualized cost (TAC) for synthesis of HEN with multi-period operation. The model allows performing a trade-off between investment and operating cost and it was applied separately for each period of operation. An algorithmic procedure is used to generate automatically the final multi-period HEN. The model MINLP does not consider the isothermal mixing. The temperature difference in both ends of each heat exchanger is calculated with true inlet and outlet temperatures in each heat transfer device. It was included an equality constraint in the calculation of temperature difference in both ends of each heat exchanger. It ensures that temperatures are exactly calculated and a relaxed constraint does not exist concerning these calculations, like in others models presented in the literature, which can overdesign the heat exchanger area. Besides, a constraint was created to ensure that no calculated area is lower than 1 m2 in order that the achieved result has practical feasibility. For the configuration of the HEN control system, it was used the Relative Gain Array (RGA) and Disturbance Cost (DC) index. Examples were utilized to test the performance of the developed procedures and satisfactory and better results than those found in the literature were obtained.